MODERN STATE OF THE REPRODUCTIVE SYSTEM OF GOLDEN MULLET (LIZA AURATA, RISSO) AT THE WESTERN PART OF THE CASPIAN SEA - D. A. Gavrilova; A. S. Abdusamadov; A. V. Dubovskaya; P. S. Taibov (Юг России: экология, развитие, 2017)
Aim. For the purpose of the assessment of golden mullet reproduction scientists have studied golden mullet fish distribution in the Western part of the Caspian Sea and determined biological indexes of spawners and the state of gonads before spawning.Methods. Collection and processing of ichtyological data was carried out according with the “Guide on materials collection and pre-processing of water biological bio-resources of the Caspian basin and their habitat”. Histological preparations of ovaries at the VI-th mature stage were fixed in Buena’s mixture; microscopic sections of gonads were colored by sour rosein with the Mallory’s method.Results. The researches have shown, that during the period 2009-2013 the golden mullet fish migration to the Russian part of the Caspian Sea was started in spring. In 2012-2013 spawners with higher biological indexes than in preceding year were the basis of sexually mature of the population. The terms of the golden mullet fish reproduction were different every year. The results of the histhological researcher noted to the partial resorption of oocytes in ovaries of females.Main conclusions. The golden mullet females aged 4-10 years (with the central group aged 6-8 years) with high linearweighting characteristics and fatness participated in spawning in 2012-2013. Pronounced changes of the oogenesis were observed in 2012. In 2013 the mass reproduction of the golden mullet was started earlier, but frequency of occurrence of the females with the caviar resorption was decreased. The comparative analysis indicated about the heightened reproductive capacity of the golden mullet fish population in 2013.